Effects of Formulation Parameters on the Characteristics of Biodegradable Microspheres of Goserelin Acetate - Kakade, Suhas Marutirao (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The purpose of this study was to develop biodegradable microspheres controlling drug delivery for treatment of prostate and breast cancer. The effects of formulation parameters on the characteristics of microspheres were studied. Material and Methods: Emulsification/extraction method was used to prepare goserelin acetate controlled-release poly(D, L-lactide-co-glycolide) (PLGA)-based biodegradable microspheres. Microspheres were formulated and characterized in terms of encapsulation efficiency, particle size distribution, surface morphology, and drug release profile. Results and Discussion: Preparative variables such as concentrations of stabilizer, drug–polymer ratio, stirring rate, and the ratio of internal to external phases were found to be important factors for the preparation of goserelin acetate-loaded PLGA microspheres. These changes were also reflected in drug release profile. Conclusion: The in vitro goserelin acetate release study from PLGA microspheres proved that the present microspheres had the properties of an ideal controlled release formulation for anticancer therapy.